Walking propulsion generation in double stance by powered exoskeleton for paraplegics - Hyun, Dong Jin; Lim, Hyunseop; Park, SangIn; Yoon, JuYoung; Jung, Kyungmo; Bae, KiHyeon; Lee, Inju (Robotics and autonomous systems, 2019)
This paper introduces an electric Hyundai Medical Exoskeleton (H-MEX). It is specially designed to enable disabled people (e.g. spinal cord injury individuals below T10, stroke patients) to walk again, according to a basic walking control strategy. H-MEX is easily assembled with mechanically/electrically block-by-block connections, and its built-in control framework provides an unique control interface. Through this interface, the H-MEX wearer can customize gait parameters (viz., the step length, step period, and default torso tilt angle). With the proposed framework, trajectories for each active joint are planned for generating propulsion (i.e., angular momentum) in double-stance gait. This facilitates stability and convenience for H-MEX wearers. A dynamic simulation was conducted on a simplified planar model that describes an average human body: the intended propulsion generation during the double-stance phase was verified to lead to angular momentum with respect to a leading stance leg, for more stable and convenient step walking. Also, the degree of propulsion was shown to be adjusted by setting kinematic percentage of intended double-stance motion. The proposed control method was evaluated with five healthy subjects on a treadmill as one of initial performance tests: kinematic data on subjects’ torsos given from basic walking at a velocity of 0.7 km/h and 1.2 km/h indicated the effectiveness of the proposed control strategy.